Single-Molecule Sensing of an Anticancer Therapeutic Protein-Protein Interaction Using the Chemically Modified OmpG Nanopore - Hwang, Hye Jin; Kim, Jin Sik; Lee, Jeonghyun; Min, Jun Sik; Jeong, Ki Baek; Kim, Eunha; Lee, Mi Kyung; Chi, Seung Wook (Analytical Chemistry, 2022)
Nanopore sensors are a highly attractive platform for single-molecule sensing for sequencing, disease diagnostics, and drug screening. Outer membrane protein G (OmpG) nanopores have advantages for single-molecule sensing owing to their rigid monomeric structure, which comprises seven flexible loops, providing distinct gating patterns upon analyte binding. Blocking of the protein-protein interaction between B-cell lymphoma-extra-large (Bcl-xL) and the BH3 domain of Bcl-2 homologous antagonist/killer (Bak-BH3) has been reported as a promising strategy for anticancer therapy. Here, we characterized the interaction between Bcl-xL and Bak-BH3 as well as its inhibition by a small-molecule inhibitor using click chemistry-based Bak-BH3 peptide-conjugated OmpG nanopores. The binding of Bcl-xL to Bak-BH3 generated characteristic gating signals involving significant changes in the amplitudes of noise and gating parameters such as gating frequency, open probability, and durations of open and closed states. Notably, specific inhibition of Bcl-xL by the small-molecule antagonist, ABT-737, led to the recovery of the noise and gating parameters. Collectively, these results revealed that the chemically modified OmpG nanopore can serve as a valuable sensor platform for ultrasensitive, rapid, and single-molecule-based drug screening against protein-protein interactions, which are therapeutic targets for various diseases.
Keywords: Anti-cancer therapeutics; B-Cell Lymphoma; Chemically modified; Disease diagnostics; Drug-screening; Outer membrane protein; Protein G; Protein-protein interactions; Single molecule; Therapeutic protein